2019
DOI: 10.1038/s41598-019-48017-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin use is associated with reduced risk for recurrence of pyogenic liver abscess: a propensity score analysis

Abstract: Aspirin possesses anti-bacterial activity that may prevent recurrence of Klebsiella pneumoniae pyogenic liver abscess (KP-PLA). In e x-vivo study, aspirin was administered before bactericidal assay against serotype K1 K. pneumoniae . We identified 5,912 patients with PLA who had no known pre-existing hepatobiliary diseases or malignancy in Taiwan from 1999 to 2013 from nationwide cohort study. Multivariate Cox proportional hazards regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Compared to male patients, female patients had a lower incidence of PLA, not only in our study but also in previous studies using the Taiwan NHIRD 6 , 18 . Biliary tract disease was reported to be associated with PLA and was much more likely to be associated with polymicrobial infections, including Escherichia coli, Enterococcus and Klebsiella species 6 , 35 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Compared to male patients, female patients had a lower incidence of PLA, not only in our study but also in previous studies using the Taiwan NHIRD 6 , 18 . Biliary tract disease was reported to be associated with PLA and was much more likely to be associated with polymicrobial infections, including Escherichia coli, Enterococcus and Klebsiella species 6 , 35 .…”
Section: Discussionsupporting
confidence: 82%
“…Therapeutic drugs administered for some chronic diseases may affect the recurrence of PLA in diabetic patients. Our previous study have demonstrated that aspirin could reduce the recurrence rate of PLA 18 . Aspirin can trigger lipoxin and enhances macrophage phagocytosis of bacteria 19 .…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that ASA can reduce capsule polysaccharide production by up to 70% [ 75 ], which resulted in the primary mechanism behind K. pneumoniae serotype K1′s increased susceptibility to leukocyte phagocytosis, preventing more invasive infections [ 76 ]. Liu et al identified 5912 patients with PLA and evaluated recurrence PLA rates between ASA users and non-users, which were 42.5 and 74.6 per 1000 person-years of follow-up, respectively [ 77 ]. Similar findings were reported in a large cohort of diabetic patients, with ASA continuous intake for >90 days associated with a lower risk of PLA [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, being a retrospective study, we were unable to systematically record the medications of patients after discharge. Therapeutic drugs administered for some chronic diseases may affect the recurrence of PLA; for example, studies have shown that aspirin can reduce the recurrence rate of PLA [24]. In addition, the patients in this study were all from a province in Northeastern China, and the epidemiology of KP may be influenced by geographic factors.…”
Section: Discussionmentioning
confidence: 99%